Time delayed control of structural systems. - Udwadia, Firdaus
Time delays are ubiquitous in control systems. They usually enter because of the sensors and actuators used in them. Traditionally, time delays have been thought to have a deleterious effect on both the stability and the performance of controlled systems, and much research has been done in attempting to eliminate them, compensate for them or nullify their presence. In this paper we take a different view. We investigate whether purposefully injected time delays can be used to improve both the system's stability and performance. Our analytical, numerical and experimental investigation shows that this can indeed be done. Analytical results of the effects of time delays on collocated and non collocated control of classically damped and non classically damped systems are given. Experimental and numerical results confirm the theoretical expectations. Issues of system uncertainties and robustness of time delayed control are addressed. The results are of practical value in improving the performance and stability of controllers because these characteristics (performance and stability) improve dramatically with the intentional injection of small time delays in the control system. The introduction of such time delays constitutes a 'minimal change' to a controller already installed in a structural system for active control. Hence, from a practical standpoint, time delays can be implemented in a nearly costless and highly reliable manner to improve control performance and stability, an aspect that cannot be ignored when dealing with the economics and safety of large structural systems subjected to strong earthquake ground shaking.
Keywords: Time delayed control; Structural systems; Collocated and non collocated control; Classically damped and non classically damped systems; Stability; Theory; Experiment and simulations; Uncertain systems and time delays